ANALISIS PEMANFAATAN LAHAN UNTUK PENGEMBANGAN BAHAN AJAR IPS (Studi Kasus pada Materi Pelestarian Lingkungan Hidup di SMP Kecamatan Argapura Kabupaten Majalengka) - Yanti, Enok (Jurnal Pendidikan Geografi Gea, 2016)
The research aims at analyzing the land use by farmers, identifying the causes, knowing the relationship of the students’ understanding with their attitudes, and formulating materials about using of land on environmental preservation materials. The method is descriptive analytic. Data were collected through field surveys, interviews, literature studies and documentation. The population includes farmers, eighth grade students and MTs teachers in Argapura District. Farmer samples were randomly stratified, learners were taken using a proportional random sampling and teacher samples were the whole population. Data were analyzed using percentages and simple and multiple linear regression. The results show that the land use in the Argapura District was largely incompatible with the slope and the frequency of attending counseling as a causative factor of land use has a negative significance level. Students’ understanding of the land condition is parallel with their attitude towards land use so learning materials should be suited to the conditions of their environment to produce meaningful learning. It is recommended that the land use follow the environmental land management rules to preserve the environment, and existing materials were only concepts. Therefore further research should be on land use materials on environmental preservation materials in Class VIII Semester 1. Keywords: Land use, teaching materials, preservation of the environment.